Heat resistance of aspergillus Sp isolated from suman sa ibos - Dela Cruz, Israel Quinsay; Francisco, Ma. Leonora dL. (2004., 2004)
ABSTRACT Four fungal isolates were identified from spoiled suman sa ibos stored at ambient temperature using acidified Potato Dextrose Agar. Morphological and cultural examinations revealed that two isolates were species of genus Aspergillus, one of Rhizopus sp and another possessed characteristics peculiar to non-filamentous Saccharomyces sp. Screening by different pasteurization temperatures (60°C, 65°C, 70°C, and 80°C) revealed Aspergillus sp as the most heat resistant amongst the four fungal cultures. Conidia of Aspergillus sp, isolated from spoiled suman sa ibos, were tested for heat resistance in neutral phosphate buffer. D values at 54°C, 52°C and 49°C were 3.01, 7.77 and 55.02 minutes respectively. Zvalue was 8.8°F. Thermal resistance studies confirmed the importance of isolated mycoflora in post-production practices, handling, and storage rather than during processing of suman sa ibos.
Thesis (BSFT)--University of the Philippines, Diliman
Keywords: Aspergillus; Snack foods -- Microbiology